2014
DOI: 10.1021/ja5041539
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Formation of One-Dimensional Hydrogen Gas Hydrate in Carbon Nanotubes

Abstract: We present molecular dynamics simulation evidence of spontaneous formation of quasi-one-dimensional (Q1D) hydrogen gas hydrates within single-walled carbon nanotubes (SW-CNTs) of nanometer-sized diameter (1−1.3 nm) near ambient temperature. Contrary to conventional 3D gas hydrates in which the guest molecules are typically contained in individual and isolated cages in the host lattice, the guest H 2 molecules in the Q1D gas hydrates are contained within a 1D nanochannel in which the H 2 molecules form a molecu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
50
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(53 citation statements)
references
References 62 publications
2
50
1
Order By: Relevance
“…2). The adsorption energy curves for a water molecule outside (6,6) CNT are very similar to those for water outside (4, 4) and (5, 5) CNTs and show nearly no curvature effects. Note that the adsorption energies of water outside (n, n) CNTs, see Table 1 also for larger CNTs, are close to the results of a water molecule adsorbed on a graphene surface, including the energy differences between Ù-and Ú-configurations which are 2123 and 2108 meV, respectively.…”
Section: Resultsmentioning
confidence: 70%
See 2 more Smart Citations
“…2). The adsorption energy curves for a water molecule outside (6,6) CNT are very similar to those for water outside (4, 4) and (5, 5) CNTs and show nearly no curvature effects. Note that the adsorption energies of water outside (n, n) CNTs, see Table 1 also for larger CNTs, are close to the results of a water molecule adsorbed on a graphene surface, including the energy differences between Ù-and Ú-configurations which are 2123 and 2108 meV, respectively.…”
Section: Resultsmentioning
confidence: 70%
“…As an alternative, we aim here at obtaining reliable force field parameters by fitting effective water-CNT and water-graphene potentials to DF-LCCSD(T) results. To this end, we use the approximation of pairwise additive LJ potential energy functions which are often used to model nonbonded interactions and which served as a basis for almost all of the previous MD simulations of water confined in CNTs, see, for example, [5,6,9,12,13,15,18,23,31,33,36,37,54] : (6,6) CNT. The PBE-D2/D3 are from periodic calculations using VASP.…”
Section: Configurationsmentioning
confidence: 99%
See 1 more Smart Citation
“…[10][11][12][13][14][15][16][17][18][19][20][21][22][23] However, microscopic mechanism of the nucleation and growth of bulk clathrate hydrate is still not fully understood. [24][25][26][27][28][29][30][31][32][33] Moreover, the host cages formed in low-dimensional clathrate hydrates differ from those in bulk clathrate hydrates due to geometric constraints. 21 Recently, several simulation studies have shown that low-dimensional clathrate gas hydrates, as well as guest-free hydrates, can be formed spontaneously on the time scale of nanoseconds in highly confined environment.…”
Section: Introductionmentioning
confidence: 99%
“…Some of the issues they bring about have already been extensively discussed and ultimately solved. Both the supposed negative infinite energy ground state and the parity eigenstates for the problem have been shown to be nonexistent on mathematical grounds using techniques that are very important for both ID systems and their applications [3][4][5][6][7][8][9][10][11][12],z lx | is not self-adjoint [13], but GW do not seem to pay enough attention to this crucial fact and its consequences [10]. Let us recall that conservation of probability is a direct consequence of the self-adjointness of the Hamiltonian according to Stone's theorem [14].…”
mentioning
confidence: 99%